PENGARUH PEMBERIAN FRAKSI ETIL ASETAT HERBA MENIRAN (Phyllanthus niruri L.) TERHADAP PENINGKATAN MEMORI DAN FUNGSI KOGNITIF PADA MENCIT GALUR BALB/C BERDASARKAN PASSIVE AVOIDANCE TEST - , DONA SARI PRATIWI, Dr. Arief Nurrochmad, M.Si., M.Sc., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Memory or the memory is the mental ability to recall sensations , impressions and ideas . The population distribution of cognitive impairment in the world and in Indonesia showed an increase . The higher the age , the prevalence of cognitive impairment will be even greater . Reduced the ability of a person's memory can be caused by degenerative processes due to several factors: age, stress , or from external pathogens such as ethanol . The damage caused by free radicals or reactive oxygen species ( ROS ) is the most popular theory and common , is associated with a wide variety of neurodegenerative diseases and aging . Herba meniran ( Phyllanthus niruri L. ) is a herb that has antioxidant flavonoid that can be used as free-radical scavengers . Ethyl acetate fraction meniran herbs can be used to prevent oxidative damage induced 10 % ethanol . The method used is the passive avoidance test . Test animals used were mice strains Balb / C. The method is divided into a training period for 4 days prior to treatment , and the test period is 4 days after treatment . In this study using 30 mice were divided into 6 groups: 0.5 % CMC - Na , 10 % ethanol , donepezil , ethyl acetate fraction herbaceous group meniran 100 mg , 200 mg , and 400 mg / kg . When finished using the passive avoidance test , the results will be analyzed statistically to determine the significance of each treatment group . After that will be a fixation on the brain of mice to see the correlation between the effect of ethyl acetate fraction of the amount of herbaceous meniran pyramidal cells in the CA1 hippocampus of mice. The results showed that administration of ethyl acetate fraction herbaceous meniran 100 mg , 200 mg , and 400 mg / kg demonstrated the ability to improve memory and cognitive function of mice exposed to 10 % ethanol by passive avoidance test . Effective dose mempu improve memory and cognitive function is 100 mg / kg . End of this study it can be concluded that the administration of ethyl acetate fraction herbaceous meniran able to repair brain damage due to ethanol can reduce neurodegeneration .